An experimental and numerical investigation on cycle-to-cycle variation of three different displacements single-cylinder motorcycle engines: The sequential analysis from intake to flame propagation process. (1st September 2020) - Deng, Banglin; Chen, Yangyang; Hou, Kaihong; Fu, Jianqin; Feng, Renhua
Highlights: CCVs of three motorcycle engines were investigated thoroughly by combined experiment and CFD. Large displacement engine displayed lowest COV at middle speed and load. Variation of TKE at IT is important origin of CCV for premixed combustion engines. The influence of interaction between flow center and flame center on CCV was revealed. The local flow and subsequent flame variation in transverse direction has much larger impact than in axial direction on CCV. Abstract: In this work, the cycle-to-cycle variation (CCV) of three single-cylinder motorcycle engines are investigated by experiment combined with CFD (computational fluid dynamics) simulation. The experimental results show that under low load (40%) as the speed increases, the CCV increases more quickly for large displacement engines. COVPmax increases by 12.5% when the speed rises from 3000 rpm to 7000 rpm for 125 ml engine, while this increase rises to 127.3% for 500 ml engine. Under high loads, the influence of speed on CCV is more obvious for small displacement, at 100% load the COVPmax of 125 ml decreases by 105.6%, while 300 ml and 500 ml increase very gently also from 3000 rpm to 7000 rpm. Then, the influences of TKE (turbulence kinetic energy), TR (tumble ratio), flow structure and internal EGR (exhaust gas recirculation) ratio on CCV were analyzed in detail through CFD. The larger displacement is, the higher TKE and smaller variation are at ignition timing, but the TR is smaller. When the distance between the flow field center and flame center is far, the CVV of flow field and the subsequent flame propagation will be amplified gradually between cycles. This investigation provides a basic understanding about the sources of CCV, the correlation between operation stability and design parameters was explored. This provides implications for the development and design of motorcycle engines.